2005
DOI: 10.1108/13639510510597861
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of alcohol consumption rates of first‐year Australian police officers

Abstract: Purpose -To prospectively investigate the alcohol consumption and health-related behaviours of Australian police officers. Design/methodology/approach -Demographic, work environment, general health and wellbeing, and alcohol consumption measures were obtained from 100 Australian police officers at two time points; the first as they underwent initial training before the commencement of operational policing duties (time 1), and the second after they had completed 12 months of operational duties (time 2). Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, in the assessment of alcohol use, many studies concerning alcohol problems have used different self-report screening instruments (Richmond et al, 1998;Romelsjö et al, 1992;Smith, 2007;Swatt et al, 2007;Vahtera, Poikolainen, Kivimäki, Ala-Mursula, & Pentti, 2002;Vasse, Nijhuis, & Kok, 1998). This has often been the Alcohol Use Disorders Identification Test (AUDIT), which shows how much alcohol a person consumes (Ahola et al, 2006;Davey et al, 2001;Frone, 1999;Grunberg et al, 1999;Lindsay & Shelley, 2009;Obst et al, 2001;Rallings et al, 2005). Different reasons for drinking have been studied (Davey et al; Grunberg et al), but as far as we know, the items have never included work-related violence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the assessment of alcohol use, many studies concerning alcohol problems have used different self-report screening instruments (Richmond et al, 1998;Romelsjö et al, 1992;Smith, 2007;Swatt et al, 2007;Vahtera, Poikolainen, Kivimäki, Ala-Mursula, & Pentti, 2002;Vasse, Nijhuis, & Kok, 1998). This has often been the Alcohol Use Disorders Identification Test (AUDIT), which shows how much alcohol a person consumes (Ahola et al, 2006;Davey et al, 2001;Frone, 1999;Grunberg et al, 1999;Lindsay & Shelley, 2009;Obst et al, 2001;Rallings et al, 2005). Different reasons for drinking have been studied (Davey et al; Grunberg et al), but as far as we know, the items have never included work-related violence.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, police officers' alcohol consumption is more hazardous and harmful than that of the general population (Anshel, 2000;Clair, 2006;Swatt et al, 2007). Alcohol abuse has also been found to be a problem among police officers in the UK (Rees & Smith, 2008;Richmond et al, 1998), and Australia (Davey et al, 2001;Rallings, Martin, & Davey, 2005;Smith 2007). In the USA, 23 per cent of police officers (Swatt et al), in Australia, 32 per cent (Obst et al, 2001), and in the UK 48 per cent of male and 40 per cent of female police officers (Obst et al) have serious drinking problems.…”
Section: Introductionmentioning
confidence: 99%
“…Not all substance use research has revealed consistent findings however, with some investigations suggesting that alcohol consumption among law enforcement officers may vary over time. In a longitudinal study for example, Rallings et al (2005) found that the proportion of Australian police who drank alcohol at harmful levels rose from 9 per cent to 17 per cent during the first 12 months of operational duties.…”
Section: Alcohol Consumptionmentioning
confidence: 99%
“…Alcohol consumption among police may not be constant, however, and probably varies over time. In a longitudinal study for example, Rallings, Martin and Davey (2005) found that the proportion of Australian police who drank alcohol at harmful levels rose from 9 per cent to 17 per cent during the first 12 months of operational duties. A similar investigation of police recruits from their first day in the academy through to one year into training also suggested that the risk of harm from alcohol consumption probably increases over time , with a tendency towards heavier drinking sessions (Obst & Davey, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation